Predicting the effect of disability on employment status and income. - Randolph DS (Work, 2004)
Research shows that participation in employment contributes to life satisfaction for persons with disabilities [18]. Title I of the Americans with Disabilities Act (ADA) sought to prohibit discrimination against persons with disabilities in the workplace, however, the ADA's effectiveness remains controversial. This research utilizes data from the disability supplement of the 2000 Behavioral Risk Factor Surveillance System to examine the impact of disability status on predicting employment status and income. Confounding variables such as gender, age, educational level, race and marital/parental status are examined regarding their influence on results. Results from analysis utilizing zero-order correlation, linear and logistic regression analysis techniques revealed that disability status has a significant predictive effect on inability to work. Furthermore, results continue to show that despite legislation, the higher the level of disability, the lower the employment status (those employed for wages) and income. Finally, disability status, coupled with being female or decreased educational level, consistently shows significance in predicting lower employment status and income than men or non-minorities with disabilities. Future research opportunities and policy implications are discussed with regard to the results presented.